Defining the Blue Economy in an Arctic Fisheries and Aquaculture Context: Insights from International Experience - Tsiouvalas, Apostolos; Raspotnik, Andreas (Журнал «ЭКО», 2022)
The paper is intended to show how the idea of the “blue economy” is conceptualized in the three main Arctic coastal regions: Northern Norway, the Russian Arctic Zone and Alaska (USA). This is done through the example of how fisheries and aquaculture function in these three regions and through an analysis of their official policies. The paper examines the current organization of blue economy management, identifying weaknesses and best practices in the three regions in question. In addition, the paper seeks to draw conclusions and trace best practices that contribute to the development of a unified concept of the “all-Arctic blue economy structure” and pave the way to the institutionalization of cross-border synergies.